Humāyūn-nāma : Tārīkh-i manẓūm, Nīma-yi nukhust - mujallad-i yakum u duwum - Zajjājī, Ḥakīm, (Miras Maktoob, ISBN: 9789004365452., 2019)
The author of this epic poem, Ḥakīm Zajjājī (alive in 676/1277), was a glassmaker who also had a talent for poetry. At some point, for reasons that remain unexplained, his life took a turn for the worse. He lost all his friends, and his wife became estranged from him. It is in this period of emotional distress that he decided to break with his previous life and move to the Charandāb district of Tabriz. This district was home to the famous house of Juwaynī, whose members held high administrative offices under the Saljūqs, the Khwārazmshāhs and Īl Khānids. Zajjājī hoped to attract the attention of this family with his masnavi, in order for them to get him out of his miserable situation. For twenty years he worked on this versified history of Islam from its earliest times until his own day. Edition of part one, part two having been published seven years earlier by the same scholar.